Combination Therapy with Lamivudine and Adenovirus Causes Transient Suppression of Chronic Woodchuck Hepatitis Virus Infections - Zhou, Tianlun (American Society for Microbiology, 2000)
Treatment of hepatitis B virus carriers with the nucleoside analog lamivudine suppresses virus replication. However, rather than completely eliminating the virus, long-term treatment often ends in the outgrowth of drug-resistant variants. Using woodchucks chronically infected with woodchuck hepatitis virus (WHV), we investigated the consequences of combining lamivudine treatment with immunotherapy mediated by an adenovirus superinfection. Eight infected woodchucks were treated with lamivudine and four were infected with ∼10(13) particles of an adenovirus type 5 vector expressing β-galactosidase. Serum samples and liver biopsies collected following the combination therapy revealed a 10- to 20-fold reduction in DNA replication intermediates in three of four woodchucks at 2 weeks after adenovirus infection. At the same time, covalently closed circular DNA (cccDNA) and viral mRNA levels both declined about two- to threefold in those woodchucks, while mRNA levels for gamma interferon and tumor necrosis factor alpha as well as for the T-cell markers CD4 and CD8 were elevated about twofold. Recovery from adenovirus infection was marked by elevation of sorbitol dehydrogenase, a marker for hepatocyte necrosis, as well as an 8- to 10-fold increase in expression of proliferating cell nuclear antigen, a marker for DNA synthesis, indicating significant hepatocyte turnover. The fact that replicative DNA levels declined more than cccDNA and mRNA levels following adenovirus infection suggests that the former decline either was cytokine induced or reflects instability of replicative DNA in regenerating hepatocytes. Virus titers in all four woodchucks were only transiently suppressed, suggesting that the effect of combination therapy is transient and, at least under the conditions used, does not cure chronic WHV infections.